Genetic Variants of the MIF Gene and Susceptibility of Rectal Cancer - Chuo D; Lin D; Yin M; Chen Y (Dove Medical Press, 2021)
Dongyu Chuo, Dapeng Lin, Mingdi Yin, Yuze Chen Colorectal Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, Shenyang, Liaoning Province 110042, People’s Republic of ChinaCorrespondence: Yuze ChenColorectal Surgery, Cancer Hospital of China Medical University, Liaoning Cancer Hospital & Institute, No. 44 Xiaoheyan Road, Dadong District, Shenyang, Liaoning Province 110042, People’s Republic of ChinaTel/Fax +86-24-31916243Email chen_yuze@aliyun.comBackground: Rectal cancer (RC) has been documented to be a highly invasive malignant neoplasm worldwide. Macrophage migration inhibitory factor (MIF) is a multifunctional cytokine involved in cell-mediated immunity, immunoregulation, inflammation. In vitro and in vivo studies have identified that MIF was involved in the carcinogenesis and progression of RC.Patients and Methods: This case–control study evaluated associations of genetic variants of the MIF gene and serum level of MIF with susceptibility of RC.Results: We found MIF level was associated with an increased risk of RC (OR for per unit: 1.38, 95% CI:1.32– 1.44; P <  0.001). Both MIF rs2012133 (OR = 1.30; 95% CIs = 1.08– 1.58; P = 0.007) and rs755622 (OR = 1.45; 95% CIs = 1.15– 1.82; P = 0.002) were significantly associated with increased risk of RC. Besides, we also found MIF rs5844572 was significantly associated with increased susceptibility of RC, with OR for per CATT repeat of 1.28 (95% CIs: 1.16– 1.41; P < 0.001). Further, we found all three variants of the MIF gene, rs5844572, rs2012133 and rs755622, could increase serum level of MIF.Conclusion: This study suggests that MIF plays an important role in the carcinogenesis of RC and could be used as a biomarker for early detection and prediction of RC.Keywords: rectal cancer, genetic, MIF, susceptibility, case–control